2020
DOI: 10.4084/mjhid.2020.033
|View full text |Cite
|
Sign up to set email alerts
|

Delivery in asymptomatic Italian woman with SARS-CoV-2 infection.

Abstract: Citation: De Socio G.V., Malincarne L., Arena S., Troiani S., Benedetti S., Camilloni B., Epicoco G., Mencacci A., Francisci D. Delivery in asymptomatic italian woman with SARS-CoV-2 infection. Mediterr J Hematol Infect Dis 2020, 12(1): e2020033, DOI: http://dx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 5 publications
0
26
0
Order By: Relevance
“…Twenty-eight case reports, [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][32][33][34][36][37][38][39][40]42,43,45 and nine retrospective case series. [27][28][29][30][31]35,41,44,46 These report articles were included for narrative analysis.…”
Section: Study Designsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty-eight case reports, [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][32][33][34][36][37][38][39][40]42,43,45 and nine retrospective case series. [27][28][29][30][31]35,41,44,46 These report articles were included for narrative analysis.…”
Section: Study Designsmentioning
confidence: 99%
“…The included studies were reports from Australia (n = 1), 32 Belgium (n = 1), 33 Canada (n = 1), 34 China (n = 21), 12,13,[18][19][20][22][23][24][25][26][27][28][29][30][31][41][42][43][44][45][46] Germany (n = 2), 14,35 Italy (n = 6), 10,11,21,[36][37][38] Jordan (n = 1), 39 Singapore (n = 1), 17 Turkey (n = 2), 16,40 and the Republic of Korea (n = 1). 15 No additional information was available on the setting characteristics of the cases described.…”
Section: Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, this review has revealed evidence for antibodies (IgG/IgM) against SARS-CoV-2 among infants tested negative for COVID-19 but born to COVID-19 mothers. Antibodies were quanti ed in 11 infants [13][14][15][16][17][18] , where 10 out of 11 infants (90.9%) had IgG/IgM against SARS-CoV-2. One infants whose antibodies were not detected tested positive for COVID-19 13 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the detection of immunoglobulin (IgM/IgG) against SARS-CoV-2 IgG and IgM among infants born COVID-19 con rmed mothers but themselves tested COVID-19 negative have been reported [13][14][15][16][17][18] . This serological evidence raises more concern about the possible mother to child transmission of antibodies against SARS-CoV-2 8,9 .…”
Section: Introductionmentioning
confidence: 99%